Analisis Pemahaman Guru Raudhatul Athfal tentang Aspek Perkembangan Nilai Agama dan Moral, Kognitif dan Fisik-Motorik di Kota Palangka Raya - Hikmah, Nor; Saudah, Saudah; Muzakki, Muzakki (Faculty of Education and Teacher Training of UINSI Samarinda, 2024)
The purpose of this study is to describe: 1) The teacher's understanding of religious and moral values for children aged 4-5 years; 2) The teacher's understanding of the cognitive abilities of children aged 4-5 years; and 3) The teacher's understanding of the physical-motor skills of children aged 4-5 years. This study uses a type of qualitative research. The data subject in this study amounted to 1 person, namely the class A1 teacher at RA Perwanida 2. In addition, the document data in this study were in the form of photographs, videos during learning, student worksheets, and one student's report book. The data collection techniques in this study were observation, interviews, and documentation. The results of this study indicate that: 1) Teachers understand aspects of the development of religious and moral values in children aged 4-5 years and can be implemented in learning activities; 2) Teachers understand aspects of cognitive development in children aged 4-5 years however, in practice the teacher's creativity has not developed to design learning activities; 3) The teacher understands aspects of physical-motor development in children aged 4-5 years through stimulation such as activities such as walking on crutches, throwing and catching balls, collage activities using sand as media, holding pencils correctly, folding makes and prayer mats, assembling and take off shoes.